Health seeking behavioral analysis associated with breast cancer screening among Asian American women - Ma GX; Gao W; Lee S; Wang MQ; Tan Y; Shive SE (Dove Medical Press, 2012)
Grace X Ma,1 Wanzhen Gao,1 Sunmin Lee,2 MinQi Wang,3 Yin Tan,1 Steven E Shive,1,41Department of Public Health, Center for Asian Health, College of Health Professions, Temple University, Philadelphia, PA, USA; 2Department of Epidemiology and Biostatistics, School of Public Health, University of Maryland, College Park, MD, USA; 3Department of Public and Community Health, University of Maryland, College Park, Maryland, MD, USA; 4East Stroudsburg University, East Stroudsburg, PA, USAObjective: The purpose of this community-based study was to apply a Sociocultural Health Behavior Model to determine the association of factors proposed in the model with breast cancer screening behaviors among Asian American women.Methods: A cross-sectional design included a sample of 682 Chinese, Korean, and Vietnamese women aged 40 years and older. The frequency distribution analysis and Chi-square analysis were used for the initial screening of the following variables: sociodemographic, cultural, enabling, environmental, and social support. Univariate and multivariate analyses were conducted on factors for breast cancer screening using multinomial logistic regression analysis.Results: Correlates to positive breast cancer screening included demographics (ethnicity), cultural factors (living in the United States for 15 years or more, speaking English well), enabling factors (having a regular physician to visit, health insurance covering the screening), and family/social support factors (those who had a family/friend receiving a mammogram).Conclusions: The results of this study suggest that breast cancer screening programs will be more effective if they include the cultural and health beliefs, enabling, and social support factors associated with breast cancer screening. The use of community organizations may play a role in helping to increase breast cancer screening rates among Asian American women.Keywords: breast cancer screening, Vietnamese, Korean, Chinese, breast cancer, Asian American